2017
DOI: 10.1177/1045389x17730930
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission sensor effect and waveform evolution during fatigue crack growth in thin metallic plate

Abstract: In this article, the effect of the acoustic emission sensor on the acoustic emission waveforms from fatigue crack growth in a thin aerospace specimen is presented. In situ acoustic emission fatigue experiments were performed on the test coupons made of aircraft grade aluminum plate. Commercial Mistras S9225 acoustic emission sensor and piezoelectric wafer active sensor were used to capture the acoustic emission waveforms from the fatigue crack. It has been shown that the piezoelectric wafer active sensor trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In a sense, the results presented in this paper are confirmed by Reference [ 48 ], where the authors described the evolution of the waves of AE signals along with the increase of the fatigue crack. It was found that the change of the shape of the AE wave was closely related to the physical condition of fracture loading and to the mechanism behind the growth of fatigue cracks.…”
Section: Discussionsupporting
confidence: 86%
“…In a sense, the results presented in this paper are confirmed by Reference [ 48 ], where the authors described the evolution of the waves of AE signals along with the increase of the fatigue crack. It was found that the change of the shape of the AE wave was closely related to the physical condition of fracture loading and to the mechanism behind the growth of fatigue cracks.…”
Section: Discussionsupporting
confidence: 86%
“…Scala [ 19 ], Pullin [ 20 ] and Awerbuch [ 21 ] investigated the fatigue of the aircraft fuselage, landing gear and other materials using AE and they demonstrated that AE is a promising technique for non-destructive evaluation of complex structures on the aircraft. Bhuiyan and Giurgiutiu performed in situ acoustic emission fatigue experiments on aircraft grade aluminum material and grouped the AE signals by waveform analysis to explain the complex phenomenon of metal fatigue [ 22 , 23 , 24 ]. Urbach demonstrated the possibility of assessing fatigue damage of blades by using the acoustic emission method based on a series of researches focusing on the process of factory tests [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the evolution of variance κ 1 and entropies S and S rev of the natural-time transformed AE time series {χ k } has been studied, where the event energy Q k is derived from the amplitude A k through the relation Q k = cA k 1.5 , where c is a constant of proportionality [51,52]. Plotting all natural-time quantities as functions of the conventional time t provides a visual way to reveal the possible entrance point to "critical stage," corresponding to the fulfillment of criticality Conditions (1) and (2). An entrance point to critical stage has been identified at time t crit = 492 h (criticality initiation time, marked by a vertical dashed line in Figure 4 and by a vertical dotted line in Figure 6), i.e., 9 h before the b-value reaches its minimum.…”
Section: B-value Versus Natural Time Analyses Of Ae Time Seriesmentioning
confidence: 99%
“…Fracture precursors in metallic [1,2] and quasi-brittle materials like rocks [3,4], concrete [5][6][7][8][9], and masonry [10,11] can be experimentally investigated focusing on the statistical properties of an acoustic emission (AE) time series from growing micro-fractures, where the discovery of underlying scaling laws suggests a description of fracture as a critical phenomenon [12][13][14][15][16][17][18][19][20][21]. Within this context, finding fracture precursors means identifying critical scaling exponents and early indicators of the approach to a critical state [22].…”
Section: Introductionmentioning
confidence: 99%